Financial Services for the Poor: Lack of Personal Identification Documents Impedes Access - Nicola Jentzsch (Weekly Report, 2009)
Without a birth certificate, no identity card can be issued and without identity card, there is no access to formal financial services. This link seems to be trivial in industrialized countries, where the ability of the individual to participate in economic life is rarely hindered by a lack of identification. In many developing countries, however, access to financial services is often denied, because potential customers cannot be identified based upon official identity documents-a basic due diligence requirement under international anti-money laundering regulations. In many developing and emerging countries, poor people have no opportunity to obtain such documents, as a large portion of the population has not been registered at birth. Without a birth certificate, however, no identity card can be issued, which is required by banks for customer identity verification. To date, the problem of identification has not played a prominent role in research concerning access to financial services. In the past, researchers have primarily focused on microfinance. In order to expand access to formal financial services, new methods for customer identification must be developed which address the realities in developing countries. Initial steps to expand access for the poor population have already been taken in countries such as India and South Africa. Aside from addressing problems associated with missing identification, it is also necessary to introduce basic financial products such as micro accounts, where the low risk associated with them is taken into account. Less demanding identification means for low-risk financial products ought to be internationally recognized and instituted in order to dispel legal ambiguities.
Keywords: K; G21; G28; 330